Transforming food systems. Impacts and insights from scaling innovations in Zimbabwe - Andriatsitohaina, Rachel Muthoni; Tsekenedza, Shylet; Mutari, Bruce; Mwenye, Dorah; Hodzi, Jonathan; Kunaka, Gamu; Chiwawa, Andrew; Chisorochengwe, Nyarai; Muhera, Shumirai; Mashiri, Patience; Mashunye, Justice; Gutsa, Freeman; et al. (Bioversity International and the International Center for Tropical Agriculture, 2022)
This is a comprehensive documentation of the processes and outcomes of food system transformation resulting from a seven-year flagship project in Zimbabwe. From a purposive selection of bean value chain actors, the authors identified and documented individual project experiences that best convey the project's outcomes from a variety of perspectives. The narratives were compared with data and information from project implementation monitoring reports, process evaluations, impact evaluations, and relevant secondary sources. Emerging solutions and outcomes for food system transformation are presented. The publication is based on the Zimbabwe flagship project jointly implemented by the Pan African Bean Alliance (PABRA) and the Zimbabwean Department of Research and Special Services (DRSS), with funding from the Swiss Development Cooperation (SDC).